Advances and novel developments in molecular allergology. Issue 12 (22nd September 2020) - Üzülmez, Öykü; Kalic, Tanja; Breiteneder, Heimo
Abstract: The continuous search for new allergens and the design of allergen derivatives improves the understanding of their allergenicity and aids the design of novel diagnostic and immunotherapy approaches. This article discusses the recent developments in allergen and epitope discovery, allergy diagnostics and immunotherapy. Structural information is crucial for the elucidation of cross‐reactivity of marker allergens such as the walnut Jug r 6 or that of nonhomologous allergens, as shown for the peanut allergens Ara h 1 and 2. High‐throughput sequencing, liposomal nanoallergen display, bead‐based assays, and protein chimeras have been used in epitope discovery. The binding of natural ligands by the birch pollen allergen Bet v 1 or the mold allergen Alt a 1 increased the stability of these allergens, which is directly linked to their allergenicity. We also report recent findings on the use of component‐resolved approaches, basophil activation test, and novel technologies for improvement of diagnostics. New strategies in allergen‐specific immunotherapy have also emerged, such as the use of virus‐like particles, biologics or novel adjuvants. The identification of dectin‐1 as a key player in allergy to tropomyosins and the formyl peptide receptor 3 in allergy to lipocalins are outstanding examples of research into the mechanism of allergic sensitization.